2022
DOI: 10.3390/jcm11123551
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren’s Syndrome-Related Organs Fibrosis: Hypotheses and Realities

Abstract: Sjögren’s syndrome (SS) is a systemic chronic autoimmune disorder characterized by lymphoplasmacytic infiltration of salivary glands (SGs) and lacrimal glands, causing glandular damage. The disease shows a combination of dryness symptoms found in the oral cavity, pharynx, larynx, and vagina, representing a systemic disease. Recent advances link chronic inflammation with SG fibrosis, based on a molecular mechanism pointing to the epithelial to mesenchymal transition (EMT). The continued activation of inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Epithelial (E)‐cadherin, known as a “cell adhesive” glycoprotein, is a single‐span transmembrane protein and is responsible for cell‐cell crosstalk and maintaining the polarity and integrity of epithelial cells. [ 26 ] E‐cadherin silencing has long been considered a key actuating factor in influencing epithelial cells to detach from each other, causing a drastic loss in cell polarity. [ 27 ] This factor can be regulated in terms of content or location by various fibrotic cytokines, including TGF‐β.…”
Section: Resultsmentioning
confidence: 99%
“…Epithelial (E)‐cadherin, known as a “cell adhesive” glycoprotein, is a single‐span transmembrane protein and is responsible for cell‐cell crosstalk and maintaining the polarity and integrity of epithelial cells. [ 26 ] E‐cadherin silencing has long been considered a key actuating factor in influencing epithelial cells to detach from each other, causing a drastic loss in cell polarity. [ 27 ] This factor can be regulated in terms of content or location by various fibrotic cytokines, including TGF‐β.…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics make AbMAs one of the best alternatives to study biomarkers, particularly in tears, given the small sample volume required, the ease of detecting various biomarkers and the good sensitivity. These issues are key when analyzing tear fluid from patients with SS, as it can be very difficult to obtain a microliter of sample due to their symptoms of ocular inflammation and DED [ 1 , 6 , 53 ], making such samples scarce and valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Sjögren’s Syndrome (SS) is a chronic autoimmune disorder characterized by lymphocyte infiltration of exocrine gland tissue throughout the body, causing dryness mainly in the eyes and mouth, but often with additional arthralgias and damage to other body systems [ 1 , 2 ]. When the clinical manifestations that occur are associated with any other well-defined auto-immune disease, the disease is referred as secondary SS.…”
Section: Introductionmentioning
confidence: 99%
“… 63 , 64 Studies in other organs have demonstrated that epithelial cells can undergo a transforming growth factor beta (TGFβ)-stimulated epithelial to mesenchymal (EMT) transition to directly participate in fibrosis through ECM production and also in the perpetuation of inflammation by increased cytokine production. 63 The cytokines IL-17 and IL-22 have been shown to drive EMT-dependent salivary gland fibrosis. 65 Further research to delineate the contribution of senescent cells to SjD pathology will provide insights into future therapeutics.…”
Section: Salivary Gland Pathologies Senescence and Saspmentioning
confidence: 99%